Joint toxic effects of galaxolide and cadmium on Carassius auratus under polluting flow conditions containing soil-water interfaces from urban areas - CHEN Fang; ZHOU Qi-xing (浙江大学学报. 农业与生命科学版, 2009)
The polluting flow containing soil-water interfaces from urban areas was simulated under laboratory conditions in order to evaluate better the toxicity of environmental pollutants in natural water. Single and joint toxicity of galaxolide and cadmium to Carassius auratus were investigated in water containing soil-water interfaces and solids-free water. The results indicate that under test condition containing soil-water interfaces, LC50 of Carassius auratus exposed to HHCB at 24, 48, 72 and 96 h was 4.81, 3.30, 2.90 and 2.55 mg·L-1, and that exposed to Cd was 43.51, 39.71, 39.01 and 38.83 mg·L-1, respectively; in solids-free water, LC50 of Carassius auratus exposed to HHCB at 24, 48, 72 and 96 h was 1.70, 1.14, 0.81 and 0.66 mg·L-1, and that exposed to Cd was 33.15, 30.06, 27.12 and 25.18 mg·L-1, respectively. Thus the single toxic effects were in the sequence HHCB> Cd. Using the 1∶1 toxicity method, under test condition containing soil-water interfaces, the joint effects of HHCB and Cd were antagonistic while the exposure time was 24 and 48 h. However, the joint effects were synergistic while the exposure time was up to 72 and 96 h. In solids-free water, the joint effects were antagonistic at 24 h. At 48, 72 and 96 h, the result of the joint effects showed synergistic. With the time prolongation, the synergistic intensity gradually increased. Apparently soil-water interfaces not only can alter the single toxic effects of HHCB and Cd on Carassius auratus but also can alter types of joint effects of the two pollutants.